Effects of chronic exposure to environmentally relevant concentrations of waterborne depleted uranium on the digestive tract of zebrafish, Danio rerio. (April 2015) - Augustine, Starrlight; Pereira, Sandrine; Floriani, Magali; Camilleri, Virginie; Kooijman, Sebastiaan A.L.M.; Gagnaire, Béatrice; Adam-Guillermin, Christelle
Abstract: Uranium is a naturally occurring element, but activities linked to the nuclear fuel cycle can increase background levels in the surrounding waters. For this reason it is important to understand how this affects organisms residing in the water column. The objective of this study was to assess histopathological effects of uranium on the gut wall of a widely used model organism: zebrafish, Danio rerio . To this end we exposed zebrafish to 84 and 420 nM depleted uranium for over a month and then examined the histology of intestines of exposed individuals compared to controls. The gut wall of individuals exposed to 84 and 420 nM of uranium had large regions of degraded mucosa. Using transmission electron microscopy (TEM) coupled to energy-dispersive X-ray spectroscopy microanalysis (EDX) we found that uranium induced a decrease in the amount of calcium containing mitochondrial matrix granules per mitochondria. This is suggestive of perturbations to cellular metabolism and more specifically to cellular calcium homeostasis. TEM-EDX of the gut wall tissue further showed that some uranium was internalized in the nucleus of epithelial cells in the 420 nM treatment. Fluorescent in situ hybridization using specific probes to detect all eubacteria was performed on frozen sections of 6 individual fish in the 84 nM and 420 nM treatments. Bacterial colonization of the gut of individuals in the 420 nM seemed to differ from that of the controls and 84 nM individuals. We suggest that host–microbiota interactions are potentially disturbed in response to uranium induced stress. The damage induced by waterborne uranium to the gut wall did not seem to depend on the concentration of uranium in the media. We measure whole body residues of uranium at the end of the experiment and compute the mean dose rate absorbed for each condition. We discuss why effects might be uncoupled from external concentration and highlight that it is not so much the external concentration but the dynamics of internalization which are important players in the game. Highlights: The study characterizes histopathological effects of uranium on the gut wall of zebrafish. Different techniques were used: microscopy, immunochemistry, fluorescent in situ hybridization. We did not find a clear dose-dependent response between individuals exposed to 84 and 420 nM uranium.